Faktor risiko diabetes melitus tipe 2 pada wanita usia subur di Kota Bekasi - Safitri, Debby Endayani; Rimbawan, Rimbawan; Dwiriani, Cesilia Meti; Khomsan, Ali; Juniantito, Vetnizah (UHAMKA PRESS, 2024)
Diabetes mellitus has a significant impact on health and, in the long term, can lead to complications. Women are at a higher risk of developing type 2 diabetes mellitus compared to men. For women of reproductive age, diabetes mellitus can affect reproductive health and pregnancy quality, which may influence the next generation. The study aimed to determine risk factors for type 2 diabetes mellitus in women of reproductive age in Bekasi City. This was matched case control study, involving 72 subjects selected by purposive sampling. The study was conducted at community health centre in Bekasi. Results: There were no significant differences in nutritional status (p=0.083) and age at menarche (p=0.234) of women of reproductive age with T2DM and non-T2DM. Long menstrual cycles increase the risk of type 2 diabetes mellitus by 6.2 times higher than normal menstrual cycles (p=0.005). A history of gestational diabetes in women of reproductive age increases the risk 2.2 times higher for women of reproductive age to experience T2DM in the future (p=0.027). Long menstrual cycles and gestational diabetes are important factors contributing to the increased risk of T2DM in women of reproductive age.